Helping to promote social justice - Harkins, Debra A (Routledge Books, 2021)
"Helping to Promote Social Justice is a richly informed and practical guide for advanced students and young professionals to become helpers capable of promoting social justice with whom they collaborate, mentor, serve and consult. Filled with insight and supplemental exercises, the book will direct readers to think critically and reflect on the broader social and political systems that create our current social injustices. Beginning with a strong theoretical focus on power, social identity, and intersectionality, the authors engage with readers' assumptions on helping, their value systems, and their understandings of power and privilege when helping communities in need. The rest of the book focuses on the application of these critical concepts, guiding future helpers to consider how to intervene, assess need, lead, build a team, address conflict and work to promote change from a position of social justice. Written by academic faculty with expertise in teaching, coaching and consulting, Helping to Promote Social Justice should be considered essential reading for students in social work, psychology and counselling"--